PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GOOGLE CLASSROOM PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR DI SMK NEGERI 3 PANGKEP - Dian Ekawati Nur; Abdul Muis Mapalotteng; Syafiuddin Parenrengi (UNM Journal of Technology and Vocational, 2021)
The study aimed to discover 1) The influence of using google classroom learning media on learning outcomes in Computer and Basic Network subject at SMKN 3 Pangkep, 2) the influence of learning motivation on learning outcomes in Computer and Basic Network subject at SMKN 3 Pangkep,and 3) the influence of using google classroom learning media and learning motivation on learning outcomes in Computer and Basic Network subject at SMKN 3 Pangkep. The research method used was ex-post facto research. The total population was 67 people. The sample size was 67 people because this study worked on the population. Data collection was conducted by using documentation and questionnaire. The prerequisite test used the normality test and linearity test. Hypothesis testing employed simple linear regression test and multiple linear regression. The results of the study reveal that: (1) students' perceptions on the use of google classroom learning media in Computer and Basic Network subject at SMKN 3 Pangkep are in "very good" category, (2) the students’ motivation in Computer and Basic Network subject at SMKN 3 Pangkep is in "very high"category, (3) the learning outcomes in Computer and Basic Network subject at SMKN 3 Pangkep are in "good" category, (4) there is an influence of using google classroom learning media on learning outcomes. The test results show that the Sig. F of 0.000 <0.05 with a contribution of 19.6%, (5) there is an influence of learning motivation on learning outcomes. The test results show that the Sig. F of 0.000<0.05 with a contribution of 41.3%, and (6) there is an influence on the use of google classroom learning media and learning motivation collectively on learning outcomes. The test results show the value of Sig. F is 0.000 <0.05 with a contribution of 45.6%. Therefore, the research hypothesis is accepted.